The Campbell of Lerags Cross at Kilbride, near Oban, with a Note on Cross-heads of Late Mediaeval Date in the West Highlands - Richardson, James S (Proceedings of the Society of Antiquaries of Scotland, 1927)
The disc-headed cross, which survived in three fragments was re-asssembled and erected in what was though to be its original location. It bears the date 1516 and carvings include the crucified saviour on the front and a heraldic shield on the back bearing the arms of Archibald Campbell. The figure of Christ is thought to have much in common with the style of French ivory carvings of the 14th century. The article includes a detailed account of the three classes of cross-heads bearing crucifixion scenes with numerous examples